NAVIGATING FINANCIAL SUCCESS: THE IMPORTANCE OF COST ACCOUNTING IN THE OIL AND GAS INDUSTRY - Atabayeva Zamira Abdujalilovna (American Journals, 2023)
This study delves into critical challenges faced by oil refineries, particularly focusing on issues such as insufficiently developed cost management systems and the intricacies surrounding the formation of production costs. It highlights the pivotal role of computerization within the production process, emphasizing its capability to effectively address modern challenges in oil refining production. The paper further explores the primary objectives of accounting within the oil and gas sector, shedding light on the necessity for robust systems that accurately capture and analyse financial data. Additionally, it discusses the pivotal role of digital information derived from automated control systems in facilitating production management, showcasing the importance of leveraging technology for informed decision-making in the industry.
Keywords: Information technology, production management, modern production, process computerization